Personalized : customer strategy in the age of AI - Abraham, Mark (Partner at BCG); Edelman, David C. (David Carl), 1961- (Boston, Massachusetts : Harvard Business Review Press, 2024)
"Research shows that the vast majority of consumers want personalized experiences, and a select few companies are rising to the challenge. These personalization leaders build trusted relationships with millions of customers across channels and engage with them at every step throughout their journey. They are rethinking their operations and unleashing the creativity of their teams-combined with the power of AI and technology-to fine-tune each successive interaction, delighting customers in the process. Most companies, though, are not doing personalization well, leading to wasted money, squandered effort, and missed expectations. To be done effectively, personalization must be a critical element of your organization's strategy. Personalized is a playbook to deliver true personalization at scale. In this book, Boston Consulting Group's Mark Abraham and Harvard Business School's David C. Edelman describe the Five Promises of Personalization that companies must live up to: Empower Me: Understand each customer's unique needs and decide how to best help them; Know Me: Win customers' trust and permission to securely use their data to improve their experience; Reach Me: Reach out to the right customer, in the right channel, at just the right moment; Show Me: Tailor unique content to be relevant to each customer, enabled by generative AI; Delight Me: Design new ways of working and processes to speed up the velocity of continuous improvement and make a customer's experience feel magical. With detailed examples across industries-including retail, health care, banking, B2B, technology, fashion, and travel-this book will help executives learn how to put personalization at the center of their strategy, accelerate growth, and capture their share of the $2 trillion personalization prize"--
The personalization advantage -- Part I: the promises of personalization -- Empower me -- Industry spotlight: travel -- Know me -- Industry spotlight: financial services -- Reach me -- Industry spotlight: retail -- Show me -- Industry spotlight: fashion and beauty -- Delight me -- Industry spotlight: health care -- Building personalization through smart integration -- Industry spotlight: B2B distribution and technology -- Part II: leading the transformation -- Expanding roles in the c-suite -- Measuring impact -- Navigating risk and privacy -- Competing on personalization -- Personalization of the future.
Includes index.
Keywords: Customer relations; Artificial intelligence